Implementation of Technology Acceptance Model to Evaluate Reliability of the New Student Selection Application Development - Agustinus Purna Irawan; Indra Widjaja (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2021)
One of the important things in university management is the selection process for new students. Management of new student admissions needs to be planned, communicated, and implemented properly to obtain new students who meet the quantity and quality targets. The selection process for new students must follow the rules contained in Permendikbud No. 3 of 2020 concerning National Standards for Higher Education in Indonesia. This study aims to develop a model for evaluating the new student selection portal that has been developed at Tarumanagara University under the name Go Untar, where the implementation refers to Permendikbud No. 3 of 2020. Go Untar has been used as a communication portal and selection of prospective new students since 2020. The method used in this study refers to the TAM (Technology Acceptance Model) model developed by Davis, 1985 and combined with the Unified Theory of Acceptance and Use of Technology model (UTAUT) by Venkatesh et.al., 2003, to obtain a combination model to evaluate Go Untar. The results shows that the TAM API 2021 model, which was developed from the modification of the two TAM models above, can be used to analyze the effectiveness and convenience of Go Untar in the selection process for new students at Tarumanagara University. The results of the model application to evaluate Go Untar application show that Go Untar application is useful for registering new students quickly and effectively, as well as able to see accurate selection results. Go Untar is easily accessible and can be used properly as a medium of communication and selection of new students, starting from account creation, data entry process, selection, and real time selection results. Go Untar is effective in facilitating digital communication between prospective new students and administrators. The results of this study will be a reference in further development. Salah satu hal penting dalam pengelolaan perguruan tinggi adalah proses penerimaan mahasiswa baru. Pengelolaan penerimaan mahasiswa baru perlu direncanakan, dikomunikasikan dan dilaksanakan dengan baik, sehingga memperoleh mahasiswa baru yang memenuhi target kuantitas dan kualitas. Proses seleksi mahasiswa baru harus mengikuti aturan yang ada dalam Permendikbud No. 3 Tahun 2020 tentang Standar Nasional Pendidikan Tinggi di Indonesia. Penelitian ini bertujuan untuk mengembangkan model untuk mengevaluasi portal seleksi mahasiswa baru yang telah dikembangkan di Universitas Tarumanagara dengan nama Go Untar, dimana implementasinya merujuk pada Permendikbud No. 3 Tahun 2020. Go Untar telah digunakan sebagai portal komunikasi dan seleksi calon mahasiswa baru sejak tahun 2020. Metode yang digunakan dalam penelitian ini merujuk pada Model TAM (Technology Acceptance Model) yang dikembangkan oleh Davis, 1985 dan dikombainasikan dengan model Unified Theory of Acceptance and Use of Technology (UTAUT) oleh Venkatesh et.al., 2003, sehingga diperoleh model kombinasi untuk mengevaluasi Go Untar. Berdasarkan hasil penelitian yang telah dilakukan dapat disimpulkan bahwa Model TAM API 2021 yang dikembangkan dari modifikasi dua model TAM di atas, dapat digunakan untuk menganalisis keefektifan dan kemudahana Go Untar dalam proses seleksi mahasiswa baru di Universitas Tarumanagara. Hasil aplikasi model yang telah dikembangkan untuk mengevaluasi aplikasi Go Untar menunjukan bahwa aplikasi Go Untar yang telah dikembangkan bermanfaat untuk melakukan registrasi dengan cepat, efektif, dan dapat melihat hasil yang akurat. Go Untar mudah diakses dan dapat digunakan dengan baik sebagai media komunikasi dan seleksi mahasiswa baru, mulai dari pembuatan akun, proses pengisian data, seleksi dan hasil seleksi yang real time. Hal ini sangat bermanfaat bagi calon mahasiswa baru dan admin untuk berkomunikasi secara digital. Hasil penelitian ini akan menjadi referensi dalam pengembangan selanjutnya.